Potassium and salicylic acid function synergistically to promote the drought resilience through upregulation of antioxidant profile for enhancing potassium use efficiency and wheat yield. (25th October 2021) - Munsif, Fazal; Farooq, Umar; Arif, Muhammad; Shah, Tariq; Jehangir, Muhammad; Zaheer, Sajjad; Akhtar, Kashif; Khan, Muhammad Shahid; Ahmad, Ijaz; Ahmad, Wiqar; Ali, Shamsher; Amir, Rabia
Abstract: Inducing tolerance against drought stress with plant growth regulator and plant nutrients is vital for ensuring food security and sustainable crop production. The present study was undertaken to assess the influence of salicylic acid (SA) either seed primed or foliar application (1.1, 2.2, 0.7 and 1.4 mM SA) coupled with potassium (K) fertilisation (0, 50 and 100 kg/ha) on wheat yield and nutrients uptake under drought stress (100% field capacity [FC], 60% FC, 30% FC) at tillering stage. Findings revealed that drought stress substantially reduced yield components, yield and grain nutrients content and uptake, whereas the potassium use efficiency (KUE) and antioxidant profile was improved. However, the foliar application of 0.7 mM SA and 1.1 mM SA as seed priming had increased number of spikes, thousand grain weight, grains per spike, grain and biomass yield, N, P, K content and K uptake, KUE and antioxidant profile both under no stress and drought stress treatments indicating the key role in ameliorating the ill effects of drought stress as compared with no SA application. Moreover, K fertilisation at 100 kg/ha had improved growth, yield and yield components, plant nutrient uptake and antioxidant profile except proline under both no stress and mild stress as compared with no K application. These results suggested that the combined use of SA either as foliar or seed primed with higher K fertilisation can substantially improve wheat yield, and grain nutritional content under mild and severe drought stresses. Abstract : K fertilisation at 100 kg/ha had improved growth, yield and yield components, plant nutrient uptake and antioxidant profile except proline under both no stress and mild stress as compare with no K application. These results suggested that the combined use of SA either as foliar or seed primed with higher K fertilisation can substantially improve wheat yield, grain nutritional content under mild and severe drought stresses.